Application of ionic‐liquid‐magnetized stirring bar liquid‐phase microextraction coupled with HPLC for the determination of naphthoquinones in Zicao. Issue 4 (21st December 2017) - Guan, Lianyue; Luo, Qiang; Shi, Jiayuan; Yu, Wei
Abstract: In this study, a green, rapid, and simple method, ionic‐liquid‐magnetized stirring bar liquid‐phase microextraction was developed for the determination of naphthoquinones, including shikonin and β, β′‐dimethylacrylshikonin, in Zicao. This method permits active magnetic stirring, extraction, and pre‐enrichment in a single device simultaneously, so the extract is conveniently collected. The analytes were extracted from the sample to ionic liquid‐magnetized stirring bar, then the analyte‐adsorbed magnetized stirring bar can be readily isolated from the sample solution by a magnet. The key experimental parameters were investigated and optimized, including the type and volume of ionic liquid, extraction time, salt concentration, stirring speed, and pH. The recoveries were in the range of 89.47–102.38%, and good reproducibilities were obtained with relative standard deviation below 5.36%. Compared with the conventional extraction methods, the proposed method is quicker and more effective.